Myocardial inefficiency is an early indicator of exercise-induced myocardial fatigue - Erevik, Christine Bjørkvik; Kleiven, Øyunn; Frøysa, Vidar; Bjørkavoll-Bergseth, Magnus; Chivulescu, Monica; Klæboe, Lars Gunnar; Dejgaard, Lars; Auestad, Bjørn; Skadberg, Øyvind; Melberg, Tor; Urheim, Stig; Haugaa, Kristina; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: The effect of prolonged, high-intensity endurance exercise on myocardial function is unclear. This study aimed to determine the left ventricular (LV) response to increased exercise duration and intensity using novel echocardiographic tools to assess myocardial work and fatigue. Methods: LV function was assessed by echocardiography before-, immediately- and 24 hours after a cardiopulmonary exercise test (CPET) and a 91-km mountain bike leisure race. Cardiac troponin I (cTnI) was used to assess myocyte stress. Results: 59 healthy recreational athletes, 52 (43-59) years of age, 73% males, were included. The race was longer and of higher intensity generating higher cTnI levels compared with the CPET (p<0.0001): Race/CPET: exercise duration: 230 (210, 245)/43 (40, 45) minutes, mean heart rate: 154±10/132±12 bpm, max cTnI: 77 (37, 128)/12 (7, 23) ng/L. Stroke volume and cardiac output were higher after the race than CPET (p<0.005). The two exercises did not differ in post-exercise changes in LV ejection fraction (LVEF) or global longitudinal strain (GLS). There was an increase in global wasted work (p=0.001) following the race and a persistent reduction in global constructive work 24-hours after exercise (p=0.003). Conclusion: Increased exercise intensity and duration were associated with increased myocardial wasted work post-exercise, without alterations in LVEF and GLS from baseline values. These findings suggest that markers of myocardial inefficiency may precede reduction in global LV function as markers of myocardial fatigue.